Models and heuristics for robust resource allocation in parallel and distributed computing systems - Siegel, Howard Jay, author; Smith, Jay, author; Janovy, David Leon, author; Maciejewski, Anthony A., author; IEEE, publisher (Colorado State University. Libraries, 2007)
This is an overview of the robust resource allocation research efforts that have been and continue to be conducted by the CSU Robustness in Computer Systems Group. Parallel and distributed computing systems, consisting of a (usually heterogeneous) set of machines and networks, frequently operate in environments where delivered performance degrades due to unpredictable circumstances. Such unpredictability can be the result of sudden machine failures, increases in system load, or errors caused by inaccurate initial estimation. The research into developing models and heuristics for parallel and distributed computing systems that create robust resource allocations is presented.
Keywords: resource allocation; parallel processing